2019
DOI: 10.2478/jvetres-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-resistant Pseudomonas aeruginosa originating from farm animals and people in Egypt

Abstract: Introduction Carbapenem-resistant Pseudomonas aeruginosa (CRPA) has become the leading cause of health care-associated infections. Treatment is difficult due to the lack of an effective antimicrobial therapy, and mortality is high. This study investigated the occurrence of CRPA in farm animals (buffaloes and cattle), livestock drinking water, and humans in Egypt. Material and Methods A total of 180 samples were examined: 50 faecal each from buffaloes and cattle, 30 of livestock drinking water, and 50 stool fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
7
23
5
Order By: Relevance
“…P. aeruginosa as an adaptive pathogens, exhibiting multidrug drug pattern is worrisome. We report 70% P. aeruginosa resistance which is in agreement with previous studies depending on the class of antibiotics [40,41]. Similar multidrug resistance P. aeruginosa has been previously reported in healthy cattle from France and elsewhere [42,43,44].…”
Section: Discussionsupporting
confidence: 92%
“…P. aeruginosa as an adaptive pathogens, exhibiting multidrug drug pattern is worrisome. We report 70% P. aeruginosa resistance which is in agreement with previous studies depending on the class of antibiotics [40,41]. Similar multidrug resistance P. aeruginosa has been previously reported in healthy cattle from France and elsewhere [42,43,44].…”
Section: Discussionsupporting
confidence: 92%
“…In Europe, Greece has a very high prevalence of carbapenem resistance in Pseudomonas (40.4% in 2015, based on the data of the European Antimicrobial Resistance Surveillance Network), which corresponds to the extensive use of these drugs [227]. Earlier reports (before 2000) highlighted the critical role of OprD inactivation and efflux pumps in carbapenem resistance, while newer reports show that carbapenemases are increasingly displaying a critical role [228]. The highly successful clone ST235 is one of the major carbapenem-resistant clones, which have spread worldwide.…”
Section: Main Mechanisms Of β-Lactam-resistance In P Aeruginosamentioning
confidence: 99%
“…In their follow up study, Wang et al [ 129 ] demonstrated clonal commonality between bla NDM -positive E. coli isolates from chicken farms, slaughterhouses, supermarkets, and humans, belonging to sequence types ST10 and ST156. Recently, another study in Egypt by Elshafiee et al [ 130 ] provided strong evidences of direct transmission of CRE to humans from farm animals. Another study by Li et al [ 124 ], investigated the prevalence, risk factors, and drivers of CRE transmission between humans and their backyard animals in rural China that provided direct evidence of inter-host transmission of bla NDM producing E. coli between humans and backyard animals.…”
Section: Molecular Epidemiology Of Carbapenem Resistance (Cr) Genementioning
confidence: 99%